El nuevo intento de los liberales costarricenses por controlar a la jerarquía católica: La tentativa del Concordato de 1894 y la reforma al artículo 36 de la Constitución en 1895 - Sandí Morales, José Aurelio (2018)
The intend of this article is to analyze two specific events related to the interaction between the leaders from the Costa Rican liberals and their homologs from the catholic church represented not only by Mgr. Thiel in Costa Rica, but also by the Holy See in Rome during the late XIX century. The main goal is to explain the true interest behind the proposal from the liberals in Costa Rica to sign the concordat in 1894. In addition it will be examined the real reasons for the regularization of religious symbols during the political campaigns modifying the 36th article of the Constitution, consequently the document tries to demonstrate how the Costa Rican government efforts were focused to overrule not only the catholic leaders but also the congregation, however the reality was very different, so at the end the government was forced to reconsider their interests based on the actual situations that took placed then, therefore they needed to give a sort of social and political freedom to the clergy.